Assessment of water quality and the impact of mining and smelting activities on the water courses of the Paz river basin - Mokrotovarova, Olga; Zuyeva, Marina; Kashulin, Nikolay (2013)
Appendix 1/15 of the publication "State of the environment in the Norwegian, Finnish and Russian border area 2007" (The Finnish Environment 6/2007).